Effect of Grape Polyphenols on Blood Pressure: A Meta-Analysis of Randomized Controlled Trials - Li, Shao-Hua; Zhao, Peng; Tian, Hong-Bo; Chen, Liang-Hua; Cui, Lian-Qun (PLOS ONE, 2015)
Background The effect of grape polyphenols on blood pressure remains unclear, which we aimed to address via a meta-analysis study. Methods We conducted study trial searches in PubMed, Embase, and the Cochrane Library databases. Summary estimates of weighted mean differences and 95% confidence intervals were obtained by using fixed-effects models. Subgroup analyses were performed to identify the source of heterogeneity. The protocol details of our meta-analysis have been submitted to the international database of prospectively registered systematic reviews (registration number CRD42015019196). Results Ten studies were included in the present meta-analysis. Our results showed daily grape polyphenol intake could significantly reduce systolic blood pressure by 1.48 mmHg when compared to control subjects (12 comparisons; -1.48 [-2.79 to -0.16] mmHg; P = 0.03). Subgroup analyses indicated larger reduction was identified in the intake of low-dose of grape polyphenols (< 733 mg/day, median level of the included studies) or patients with metabolic syndrome. Contrarily, diastolic blood pressure was not significantly decreased in the grape polyphenols group as compared to controls. No significant heterogeneity or publication bias was detected in the meta-analysis of either systolic or diastolic blood pressure. Conclusions Daily grape polyphenol intake can significantly reduce the systolic blood pressure in humans, although the reduction is modest when compared with anti-hypertensive medications. Larger, better designed trials, that specifically include hypertensive subjects, are required to verify our results in the future.